Factors affecting symptom duration and recovery among home-treated COVID-19 patients in Baghdad-Iraq: a cross-sectional study - Mazin Ghazi Al-Rubaey,; Ahmed Abdulsattar Salman, (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the prevalence of Long COVID among home-treated coronavirus disease-2019 cases, and the factors that may influence the duration of symptoms. Method: The cross-sectional study was conducted from February to July 2021 at 20 primary healthcare centres in 10 health districts of Baghdad, Iraq, after approval from the ethics review committee of the College of Medicine, Mustansiriyah University, Baghdad. Those included were adults of both genders who previously had coronavirus disease-2019 infection as diagnosed through on polymerase chain reaction test, and received supportive treatment during isolation at home. Data was collected through direct interview using a questionnaire which consisted of demographic characteristics, comorbidities, smoking history and symptoms of coronavirus disease-2019 along with their duration. Measurement of weight and height was also done for each subject. Data was analysed using SPSS 27. Results: Of the 400 participants, 248(62%) were males and 152(38%) were females. The overall mean age was 40.8±12.8 years (range: 18-71 years). Of the total, 121(30.25%) subjects had persistent symptoms for >4 weeks. The mean duration of illness was 4.2±3.6 weeks (range: 1-16 weeks). The symptoms that lasted for >4 weeks were fatigue 94(23.5%), loss of smell or taste 59(14.75%), and cough 8(2%). Age, smoking status, comorbidities and the total number of initial symptoms showed a significant association with the duration of illness (p<0.05). Conclusion: A substantial number of mild to moderate coronavirus disease-2019 cases suffered from persistent symptoms. The duration of illness could have been influenced by age, comorbidities, smoking status and total number of initial symptoms. Key Words: COVID-19, Anosmia, Taste, Smoking, Cough, Polymerase, Fatigue,